Aktivisme Digital Fandom ARMY Indonesia dalam Menanggapi Isu RUU Cipta Kerja (Omnibus Law) di Twitter - Bianca Abigail Lasut; Hedi Pudjo Santosa; Nurul Hasfi (Interaksi Online, 2021)
K-Pop fandom, especially the Indonesian ARMY fandom, is known as a network that is quite barbaric and destructive. They often show their behavior that often posts with negative words if someone has a problem with their idol or fandom. This study aims to find out what themes are displayed by fans to criticize the issue of the Job Creation Bill, how the fandom process responds to or criticizes the issue of the Job Creation Bill, as well as knowing the process or way they gather power in responding to the issue (resistance). The method used is descriptive qualitative with an interpretive approach. The theory used in this research is the theory of digital activism and participatory culture. The data obtained using the interview method with several informants and observations made online. The theme formed by the ARMY fandom to criticize the issue of the Job Creation Bill is on digital activism: activism planning, mass mobilization on Twitter, and the process of forming public opinion. Themes in participatory culture include: message consumption, participation, and content production. This research shows that K-Pop ARMY fandom is not apolitical and cares about political issues in Indonesia. The use of theory in this study still needs to be studied more deeply by further studies so as to get more varied results. The solidarity factor and the wealth of knowledge are important factors in the digital activism of a fandom.